Penilaian Risiko menggunakan Metode Failure Mode and Effects Analysis (FMEA) terkait Kontaminasi Silang pada Area Pengemasan di Industri Farmasi “XYZ” - Azzahra, Annisa Maulida (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Cross-contamination occurs due to other previously produced products, other rooms or areas producing different products, and particles from machinery or equipment. Quality risk management can be a preventive measure in reducing the potential for cross-contamination that occurs in the pharmaceutical industry. One part of quality risk management is risk assessment. One of the most common and effective methods is the Failure Mode and Effect Analysis (FMEA) method. This risk assessment is carried out using the stages of risk identification, risk analysis, and risk evaluation using categorization based on the Risk Priority Number (RPN). Based on the risk assessment using the FMEA method regarding cross-contamination in the Packaging area in the "XYZ" pharmaceutical industry, it can be concluded that the results of observations and interviews with operators and Packaging Supervisors identified 19 risks which were categorized as low, medium, high, and very high. Based on the results of the risk assessment obtained, the risk of cross-contamination that needs to be controlled is those with an RPN value of 30 ≤ RPN ≤ 60 (medium); 75 ≤ RPN ≤ 100 (high); RPN ≥ 150 (very high). Therefore, the "XYZ" pharmaceutical industry needs to determine and implement risk control measures. By adequately controlling the potential risk of cross-contamination, it will ensure the safety and quality of the products produced.